Infliximabe no tratamento inicial da retocolite ulcerativa moderada e grave. Terapia top down: Relato preliminar - Teixeira, Fabio Vieira [UNESP]; Saad-Hossne, Rogério [UNESP]; Carpi, Maurício Rampinelli; Teixeira, Ana Claudia de Aquino; Teixeira Jr., Paulo (FapUNIFESP (SciELO), 2008)
The first option for the treatment of UC is both: salicylates or corticoids. Recently, in late November of 2006, the Brazilian Ministry of Health has approved infliximab (Remicade c, Mantecorp, Brazil) to treat ulcerative colitis. We report the use of infliximab as a first option for the treatment of two patients with severe ulcerative colitis. Case report: Patient 1: AZF, 52 years-old, female, was first diagnosed with UC after history and clinical examination; colonoscopy showed pancolitis with positive biopsy (crypt microabscess). Her Mayo score was 10 (range: 0 to 12/asymptomatic to severe colitis). She received intra venous infusion of infliximab at a dose of 5mg/Kg of body weigh at week 0, 2, 6 and 14. Then, patient was given mesalazine 4.5 g/day for maintenance therapy. Clinical response was defined as a decreased from baseline in the total Mayo score of at least 3 points. At present, patient is asymptomatic with Mayo score of 3 one moth after the last dose of infliximab. Patient 2: MLA, 45 years-old, female was first diagnosed with bloody diarrhea; colonoscopy showed left colitis and the biopsy was positive for ulcerative colitis. Her Mayo score was 9. She was offered and accepted the step down treatment. She was given infliximab 5mg/Kg of body weight at week 0, 2, 6 and 14. After initial treatment with infliximab, she received mesalazine 4.2 g/day. At present, she is asymptomatic with Mayo score of 2 eighteen days after the last dose of infliximab. At our knowledge, this is the first Brazilian report of the use of infliximab as fist-line therapy in ulcerative colitis. Few days after the begging of the infusion, an impressive clinical and colonoscopy improvement was seen in these two patients. Recently, it has been reported the use of infliximab as first-line therapy in pediatric Crohn disease. Infliximab could be a good option in cases of moderate and severe UC to avoid the side effects of the use of high doses of corticoids in patients with moderate and severe UC. However, the question if step-down therapy in ulcerative colitis is better then conventional therapy with salicylates and corticoids needs to be answered by randomized trials.
Infliximab: First line therapy in severe ulcerative colitis. Preliminary report
Keywords: Infliximab; Top down therapy; Treatment; Ulcerative colitis